GENRE-BASED APPROACHES IN TEACHING AND LEARNING ENGLISH FOR ACADEMIC PURPOSES (EAP) - Aleksandrzak, Magdalena (Neofilolog, 2018)
In recent years English for academic purposes (EAP) has become one of the mainstream fields of practice, study and research within language education, mainly due to the position of English as the international language of higher education and scientific research. The paper briefly examines the main assumptions of the approach in the context of its links to ESP (English for specific purposes), systemic functional linguistics and new literacy studies. However, the main focus of the present discussion is on genre-based pedagogy as the leading framework and an important point of reference for EAP education. To illustrate this perspective within the field, the notion of genre and its interpretations in foreign language teaching are discussed. Finally, two closely related academic genres – discussion and debate – are explored with the aim of indicating their potential benefits, areas of difficulty and challenges for students and teachers in the EAP classroom.